Implementation of Human Resource Training and Development to Improve Employee Performance: A Study at Grand Rohan Hotel Yogyakarta - Hesty Renita Cahyani; Andriyastuti Suratman (International Journal of Sociology of Religion, 2025)
The purpose of this study is to determine how training and development are implemented at the Grand Rohan Hotel in Yogyakarta, the supporting factors and obstacles encountered, and the benchmarks for the success of the program. This study uses a qualitative method with a case study approach, where data is obtained through interviews, observation, and documentation. The results show that training and development play an important role in improving employee skills, motivation, and loyalty, although there are obstacles in its implementation, such as time and cost constraints. Overall, a consistent training and development program has been proven to support improved employee performance while strengthening the hotel's competitiveness.